Profitability of divisions of holding structures - Eshmamatova Madina (Research Parks Publishers, 2021)
At the present stage of economic development, for many companies, the structure, expansion of the scope of activity, and entry into new markets becomes relevant. One of the steps in the structure of restructuring of domestic enterprises is the further development of holding companies. The article examines the features and multifaceted functioning of holding companies in modern conditions, it is proposed to classify holdings according to the proposed features.